Microstructure and electrical properties of (Ta, Co, Pr) doped TiO2 based electroceramics - Sousa, V. C.; Oliveira, M. M.; Orlandi, Marcelo Ornaghi [UNESP]; Longo, Elson [UNESP] (Springer, 2010)
The addition of different dopants affects the densification, mean grain size and electrical properties of TiO2-based varistor ceramics. This paper discusses the microstructural and electrical properties of (Ta, Co, Pr) doped TiO2 systems, demonstrating that some of these systems display electrical properties that allow for their use as low voltage varistor. Dopants such as Ta2O5 play a special role in the formation of barriers at the grain boundary and in the nonlinear behavior in TiO2-based systems. The higher values of nonlinear coefficient and breakdown electric field were obtained in the system just doped with Ta2O5 and CoO.